Recent progresses on single-atom catalysts for the removal of air pollutants - Wang, Yang; Wang, Min (Frontiers in Chemistry, 2022)
The booming industrialization has aggravated emission of air pollutants, inflicting serious harm on environment and human health. Supported noble-metals are one of the most popular catalysts for the oxidation removal of air pollutants. Unfortunately, the high price and large consumption restrict their development and practical application. Single-atom catalysts (SACs) emerge and offer an optimizing approach to address this issue. Due to maximal atom utilization, tunable coordination and electron environment and strong metal-support interaction, SACs have shown remarkable catalytic performance on many reactions. Over the last decade, great potential of SACs has been witnessed in the elimination of air pollutants. In this review, we first briefly summarize the synthesis methods and modulation strategies together with the characterization techniques of SACs. Next, we highlight the application of SACs in the abatement of air pollutants including CO, volatile organic compounds (VOCs) and NOx, unveiling the related catalytic mechanism of SACs. Finally, we propose the remaining challenges and future perspectives of SACs in fundamental research and practical application in the field of air pollutant removal.